Laser printed two-dimensional transition metal dichalcogenides - Abbas, Omar Adnan (Sci Rep, 2021)
Laser processing is a highly versatile technique for the post-synthesis treatment and modification of transition metal dichalcogenides (TMDCs). However, to date, TMDCs synthesis typically relies on large area CVD growth and lithographic post-processing for nanodevice fabrication, thus relying heavily on complex, capital intensive, vacuum-based processing environments and fabrication tools. This inflexibility necessarily restricts the development of facile, fast, very low-cost synthesis protocols. Here we show that direct, spatially selective synthesis of 2D-TMDCs devices that exhibit excellent electrical, Raman and photoluminescence properties can be realized using laser printing under ambient conditions with minimal lithographic or thermal overheads. Our simple, elegant process can be scaled via conventional laser printing approaches including spatial light modulation and digital light engines to enable mass production protocols such as roll-to-roll processing.